Laplace transform of e^(at)coswt

preview_player
Показать описание
Laplace transform of e^(at)coswt

#LaplaceTransformOfe^(at)coswt
#LaplaceTransformOfe^(bt)coswt
#LaplaceTransformOfe^(ct)coswt
#LaplaceTransformOfe^(dt)coswt
#LaplaceTransformOfe^(et)coswt
#LaplaceTransformOfe^(ft)coswt
#LaplaceTransformOfe^(gt)coswt
#LaplaceTransformOfe^(ht)coswt
#LaplaceTransformOfe^(it)coswt
#LaplaceTransformOfe^(jt)coswt
#LaplaceTransformOfe^(kt)coswt
#LaplaceTransformOfe^(lt)coswt
#LaplaceTransformOfe^(mt)coswt
#LaplaceTransformOfe^(nt)coswt
#LaplaceTransformOfe^(ot)coswt
#LaplaceTransformOfe^(pt)coswt
#LaplaceTransformOfe^(qt)coswt
#LaplaceTransformOfe^(rt)coswt
#LaplaceTransformOfe^(st)coswt
#LaplaceTransformOfe^(tt)coswt
#LaplaceTransformOfe^(ut)coswt
#LaplaceTransformOfe^(vt)coswt
#LaplaceTransformOfe^(wt)coswt
#LaplaceTransformOfe^(xt)coswt
#LaplaceTransformOfe^(yt)coswt
#LaplaceTransformOfe^(zt)coswt
#LaplaceTransformOfe^(at)coswt=(s-a)/[(s-a)^(2)+w^(2)]
#LaplaceTransformOfe^(bt)coswt=(s-b)/[(s-b)^(2)+w^(2)]
#LaplaceTransformOfe^(ct)coswt=(s-c)/[(s-c)^(2)+w^(2)]
#LaplaceTransformOfe^(dt)coswt=(s-d)/[(s-d)^(2)+w^(2)]
#LaplaceTransformOfe^(et)coswt=(s-e)/[(s-e)^(2)+w^(2)]
#LaplaceTransformOfe^(ft)coswt=(s-f)/[(s-f)^(2)+w^(2)]
#LaplaceTransformOfe^(gt)coswt=(s-g)/[(s-g)^(2)+w^(2)]
#LaplaceTransformOfe^(ht)coswt=(s-h)/[(s-h)^(2)+w^(2)]
#LaplaceTransformOfe^(it)coswt=(s-i)/[(s-i)^(2)+w^(2)]
#LaplaceTransformOfe^(jt)coswt=(s-j)/[(s-j)^(2)+w^(2)]
#LaplaceTransformOfe^(kt)coswt=(s-k)/[(s-k)^(2)+w^(2)]
#LaplaceTransformOfe^(lt)coswt=(s-l)/[(s-l)^(2)+w^(2)]
#LaplaceTransformOfe^(mt)coswt=(s-m)/[(s-m)^(2)+w^(2)]
#LaplaceTransformOfe^(nt)coswt=(s-n)/[(s-n)^(2)+w^(2)]
#LaplaceTransformOfe^(ot)coswt=(s-o)/[(s-o)^(2)+w^(2)]
#LaplaceTransformOfe^(pt)coswt=(s-p)/[(s-p)^(2)+w^(2)]
#LaplaceTransformOfe^(qt)coswt=(s-q)/[(s-q)^(2)+w^(2)]
#LaplaceTransformOfe^(rt)coswt=(s-r)/[(s-r)^(2)+w^(2)]
#LaplaceTransformOfe^(st)coswt=(s-s)/[(s-s)^(2)+w^(2)]
#LaplaceTransformOfe^(tt)coswt=(s-t)/[(s-t)^(2)+w^(2)]
#LaplaceTransformOfe^(ut)coswt=(s-u)/[(s-u)^(2)+w^(2)]
#LaplaceTransformOfe^(vt)coswt=(s-v)/[(s-v)^(2)+w^(2)]
#LaplaceTransformOfe^(wt)coswt=(s-w)/[(s-w)^(2)+w^(2)]
#LaplaceTransformOfe^(xt)coswt=(s-x)/[(s-x)^(2)+w^(2)]
#LaplaceTransformOfe^(yt)coswt=(s-y)/[(s-y)^(2)+w^(2)]
#LaplaceTransformOfe^(zt)coswt=(s-z)/[(s-z)^(2)+w^(2)]
#L[e^(at)coswt]=(s-a)/[(s-a)^(2)+w^(2)]
#L[e^(bt)coswt]=(s-b)/[(s-b)^(2)+w^(2)]
#L[e^(ct)coswt]=(s-c)/[(s-c)^(2)+w^(2)]
#L[e^(dt)coswt]=(s-d)/[(s-d)^(2)+w^(2)]
#L[e^(et)coswt]=(s-e)/[(s-e)^(2)+w^(2)]
#L[e^(ft)coswt]=(s-f)/[(s-f)^(2)+w^(2)]
#L[e^(gt)coswt]=(s-g)/[(s-g)^(2)+w^(2)]
#L[e^(ht)coswt]=(s-h)/[(s-h)^(2)+w^(2)]
#L[e^(it)coswt]=(s-i)/[(s-i)^(2)+w^(2)]
#L[e^(jt)coswt]=(s-j)/[(s-j)^(2)+w^(2)]
#L[e^(kt)coswt]=(s-k)/[(s-k)^(2)+w^(2)]
#L[e^(lt)coswt]=(s-l)/[(s-l)^(2)+w^(2)]
#L[e^(mt)coswt]=(s-m)/[(s-m)^(2)+w^(2)]
#L[e^(nt)coswt]=(s-n)/[(s-n)^(2)+w^(2)]
#L[e^(ot)coswt]=(s-o)/[(s-o)^(2)+w^(2)]
#L[e^(pt)coswt]=(s-p)/[(s-p)^(2)+w^(2)]
#L[e^(qt)coswt]=(s-q)/[(s-q)^(2)+w^(2)]
#L[e^(rt)coswt]=(s-r)/[(s-r)^(2)+w^(2)]
#L[e^(st)coswt]=(s-s)/[(s-s)^(2)+w^(2)]
#L[e^(tt)coswt]=(s-t)/[(s-t)^(2)+w^(2)]
#L[e^(ut)cowwt]=(s-u)/[(s-u)^(2)+w^(2)]
#L[e^(vt)coswt]=(s-v)/[(s-v)^(2)+w^(2)]
#L[e^(wt)coswt]=(s-w)/[(s-w)^(2)+w^(2)]
#L[e^(xt)coswt]=(s-x)/[(s-x)^(2)+w^(2)]
#L[e^(yt)coswt]=(s-y)/[(s-y)^(2)+w^(2)]
#L[e^(zt)coswt]=(s-z)/[(s-z)^(2)+w^(2)]
Рекомендации по теме